(3GdfbhO hGdJhGRf GdEbJUGOj (B/s - (3eUWai, CMeO aQjOs; (3MSf, SgjQ eMeO GdSjO s ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2000)
(3GdfbhO CTcGdgG GdJGQjNjI hJWhQgG(B- (3WHjYI GdfbhO heGgjJgG(B- (3GdhXGFa GdEbJUGOjI ddfbhO(B- (3GdJbSje GdfhYj ddfbhO(B- (3CKQ GdfbhO Ydi GdeJZjQGJ GdEbJUGOjI(B- (3GdfjhcdGSjc hGdWdH Ydi GdfbhO(B- (3GdJMdjd GdfbOj dOGdI GdWdH Ydi GdfbhO(B- (3GdYhGed GdeMOOI dcejI GdfbhO(B- (3GdefGgL hGdfXQjGJ GdeNJdaI ddJhGRf GdEbJUGOj(B- (3feGPL GdJhGRf(B- (3CfXeI hGdSjGSGJ GdfbOjI(B- (3GdLgGR GdeUQaj(B- (3Shb GdeGd(B( (3HhQUI GdGhQGb GdeGdjI(B).s
Keywords: (3GdJhGRf GdEbJUGOjs; (3GdfbhOs